Strategy of Librarians in the Preservation of Library Materials : A Literature Review - Waldy Gusti Yadi, Indah Silvia, (UIN Raden Intan Lampung, 2024)
Maintaining library materials is an important part of library management because it aims to ensure that the collection remains accessible and survives for the next generation. Librarians are critical to ensuring that library materials remain safe, maintained, and relevant. The purpose of this article is to provide an overview of the literature regarding approaches that librarians can use in carrying out the task of preserving library materials. This article also discusses the role and strategies of librarians in preserving library materials through a comprehensive literature review. Preserving library materials is an important effort to maintain the continuity and availability of information for future generations. Librarians have a big responsibility in ensuring that library materials are protected from physical, chemical and biological damage. Through various literature, this article identifies various strategies used by librarians, including preventive and restorative methods, digitalization, and the use of information technology. Observation results show that collaboration between librarians, training and increasing competence, and the use of advanced technology are the keys to effective preservation efforts. Apart from that, this article also highlights the challenges librarians face in the preservation process, such as budget limitations and lack of awareness of the importance of preservation. Overall, this literature reflection provides an in-depth picture of how librarians can develop and implement effective strategies to maintain the sustainability of library materials This is a new author guideline and article template of Jurnal El-Pustaka June 2022 edition. Abstract is written briefly and factually using book Antiqua font, 10 pt with text length between 200-250 words. English version abstracts are written in past tense and in good sentences. Do not use abbreviations or citation in the abstract. Results and conclusions are written in present tense. Abstract includes problems background, research objectives, research methods, results, and conclusions.